Model Proposal: Brand Personality of Chain Drug Stores in Chile - Escobar-Farfan, M (FUNDACION UNIV KONRAD LORENZ, 2017)
This research proposes a model of brand personality in the context of Chain Drug Stores in Chile, known as Pharmacy Chains Brand Personality (PCBP). This proposal mainly considers the model developed by Aaker (1997), but adapted to the features and characteristics of the pharmaceutical industry dimensions. To identify the dimensions proposals for this study, a series of exploratory qualitative procedures such as was made: semi-structured questionnaires, interviews and focus groups, plus an extensive review of the literature. Analyzing the results, it follows that the nature of the model is multidimensional character, since it consists of five dimensions: Transparency, Ambition, Social, Sincerity and Competence. This research aims to provide a model proposal to literature, as an investigative approach to this industry, which was affected by one of the most important cases of collusion in Chile. (c) 2016 Fundacion Universitaria Konrad Lorenz. Published by Elsevier Espana, S.L.U. This is an open access article under the CC BY-NC-ND license